Prognostic value of platelet derived growth factor α receptor expression in grade 2 astrocytomas and oligoastrocytomas. Issue 6 (1st June 2002) - Ribom, D; Andræ, J; Frielingsdorf, M; Hartman, M; Nistér, M; Smits, A
Abstract : Objective: To determine whether the expression of platelet derived growth factor α receptor (PDGFRα) in low grade astrocytomas and oligoastrocytomas is associated with survival. Methods: Formalin fixed and paraffin embedded tumour samples of 40 consecutive patients with supratentorial diffuse astrocytomas and oligoastrocytomas of WHO grade 2, resected between 1986 and 1993, were used for immunohistochemical staining. The fraction of tumour cells expressing PDGFRα protein was quantified and entered into univariate and multivariate survival analyses. Changes in PDGFα expression over time were analysed in seven patients in whom reoperations had been performed. Results: Patients with a relatively high fraction of PDGFRα expressing cells had a more favourable outcome in both univariate (p = 0.04) and multivariate analyses (p = 0.02). Expression of PDGFRα was greater in oligoastrocytomas than in astrocytomas (p = 0.05). In four reoperated patients with histologically confirmed malignant transformation, there was a marked decrease in the number of cells expressing the receptor. Conclusions: There is an association between high PDGFRα expression and long survival time in patients with grade 2 astrocytomas and oligoastrocytomas. The findings suggest that expression of the receptor may be a useful prognostic marker in such patients.